ANALISA KEMAMPUAN LITERSI SAINS MAHASISWA FISIKA DALAM CAKUPAN PROSES SAINS (KATEGORI MENGGUNAKAN BUKTI ILMIAH) - Sulistiawati Sulistiawati (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2017)
One category in the scope of the science process is the category using scientific evidence. The purpose of this science literacy test is to know the extent to which students' literacy skills. The test was conducted on September 11, 2017. Respondents were Physics students who took Basic Chemistry course in the first semester. The highest student grade score was 56.5, the lowest was 17.4 with the average of 35.3 points. The results showed that the ability to use scientific evidence of students in the low category.